CONSTRUYENDO LA HISTORIA DE LA MUJER EN AMÉRICA LATINA: Hacia la consolidación de una historia integral de género - Mora Carvajal, Virginia (1994)
The article analyzes the basics factors which have influenced the development of studies about women´s history in Latin America. Likewise, their tendencies, the approached themes, as well as main theoric-methodological orientatios of these studies, are analyzed.